Spiroxys contortus (Rudolphi, 1819) and Hedruris orestiae (Moniez, 1889) in Argentine turtles - Palumbo, Ezequiel (2016)
Knowledge of parasites in turtles is scarce, particularly with regard to freshwater turtles of South America. Here, we describe the association of Spiroxys contortus (Rudolphi, 1819) in Phrynops hilarii (Duméril & Bibron, 1835) and S. contortus and Hedruris orestiae (Moniez, 1889) in Hydromedusa tectifera (Cope, 1870). The presence of S. contortus in P. hilarii represents a new host record and also the southernmost geographic record for this species. More interestingly, the presence of H. orestiae in H. tectifera represents the first record of this helminth species from a reptilian host.